Evaluate the Effectiveness of RNAi-Based Nanoparticles as Therapy for Pancreatic Cancer - Anurogo, Dito; Krit, Pong; Lek, Siri (Journal of Biomedical and Techno Nanomaterials, 2025)
Pancreatic cancer is one of the most lethal cancers with limited effective treatment options. RNA interference (RNAi) offers a promising therapeutic approach, but efficient delivery systems are essential. To evaluate the effectiveness of RNAi-based nanoparticles as a therapy for pancreatic cancer, focusing on tumor inhibition and cell viability. A comprehensive study combining in vitro, in vivo, and clinical approaches was conducted. Pancreatic cancer cell lines (PANC-1, BxPC-3, AsPC-1) and mouse models with human pancreatic tumors were treated with RNAi-based nanoparticles. Characterization of nanoparticles included size, charge, and stability assessments using DLS and HPLC. RNAi-based nanoparticles inhibited tumor growth by 70% in mouse models and reduced cell viability by 60% in vitro. Nanoparticles demonstrated high stability and effective internalization into cancer cells, leading to significant gene silencing and apoptotic effects. RNAi-based nanoparticles show significant potential as an effective therapy for pancreatic cancer, demonstrating substantial tumor inhibition and cell viability reduction. Further clinical trials are necessary to confirm these findings and optimize nanoparticle formulations.